Proceedings of the 11th Nordic Conference on Human-Computer Interaction: Shaping Experiences, Shaping Society 2020
DOI: 10.1145/3419249.3420139
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Communication between Remote Couples: Exploring the Design of Wearable Ambient Displays

Abstract: We explore the potential of limited vocabulary wearable ambient displays and their preferred characteristics in communicating intimacy between couples at a distance. The research comprises two studies: a co-design workshop and a field study of the design concepts generated from the co-design workshops using low-fidelity prototypes. Our findings reveal that wearable ambient displays could potentially help to increase awareness and emotional connections between couples. A limited vocabulary display is considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In addition, the design of the current prototype does not explicitly reveal its purpose and intended context of use to outsiders. As demonstrated by user exploration sessions, this solution might allow for creating an intimate and exclusive form of communication, thereby supporting the findings of previous works in this field [10,12,14]. These insights should be further explored in real-life settings.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In addition, the design of the current prototype does not explicitly reveal its purpose and intended context of use to outsiders. As demonstrated by user exploration sessions, this solution might allow for creating an intimate and exclusive form of communication, thereby supporting the findings of previous works in this field [10,12,14]. These insights should be further explored in real-life settings.…”
Section: Discussionsupporting
confidence: 79%
“…This motive also surfaced during the user explorations (User Exploration Theme 5: Envisioning future development), as participants would like to have an opportunity to assign text, music, or images to the rhythms. Prior research has suggested personalization as one of the key of designing for LDRs [12,14,19]. The participants would like their communication and overall experience of being in an LDR to be more exclusive, e.g., by having a form of code that is understandable just for the two of them (see CT 5: Transmitting subtle expressions and emotional states).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation